ANALISIS KESULITAN BELAJAR MATEMATIKA SISWA MATERI BANGUN DATAR SEKOLAH MENENGAH PERTAMA - Edy Waluyo; Nuraini Nuraini (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
This study aims to analyze the learning difficulties of planes materials of grade VII SMPN 1 Suralaga East Lombok.  This type of research is descriptive research with qualitative approach to describe and describe phenomena by paying attention to characteristics, quality and interrelationship between activities. Data analysis is conducted through the stages (1) identifying and grouping student errors in answering questions about flat wakeups, (2) Analyzing student error errors. The subject of this study was a grade VII student of SMPN 1 Suralaga who numbered 25 people. The research instrument used is a description test of planes material. The researchers showed that the percentage of students who answered correctly was still low. The 5 questions that must be completed, the percentage of students who answered the correct questions in a row was 48%, 32%, 44%, 35% and 40%. The results of the analysis showed that students had difficulty in solving flat wake problems, including (1) difficulties in the use of concepts, (2) difficulties in the use of principles, (3) difficulty solving problems Kata kunci: analisis, bangun datar, kesulitan